Asuhan Kebidanan Komprehensif pada Ny. P Umur 26 Tahun G2P1A0 di Wilayah Kerja PMB Mugi Musrianah Amd.Keb - Rahmadhani, Tesa Dwiputri; Cahyaningrum (Universitas Ngudi Waluyo, 2023)
Pregnancy, childbirth, postpartum and newborn babies are physiological conditions, but there are times when the process does not run smoothly, there is the possibility of experiencing a situation that threatens the life of the mother and baby and even causes death. So the government's efforts to reduce MMR and IMR are by improving comprehensive and high quality health services for mothers and babies, within the scope of midwifery, namely providing comprehensive midwifery care (continuity of care). The method used in comprehensive care for pregnant, maternity, postpartum, BBL and family planning women is a descriptive research method and the type of descriptive research used is a case study (Case Study). Based on the results of Continuity of Care-based case studies carried out from pregnancy to family planning counseling. It was found that midwifery care for Mrs.